KRISTOFORIDHI’S CONCEPT IN CLASSIFYING GHEG VOWELS - Myrta, Manola Kaçi (European Scientific Journal, ESJ, 2015)
Kristoforidhi, is a linguist and scholar who has contributed to Albanian linguistics. His work has been focus of various linguists and scholars. His interests’ studies, among others, have also included the phenomena of phonetic nature. In this study, we are focused on introducing Kristoforidhi’s concept about Gheg vowel system based in the respective classifications according to their features. Another aim of this study is Kristoforidhi’s treatment of some phonetic phenomena as elision, aphaeresis, rounded, diphthongs and consonants exchanges. Foreign researchers, who also presented their concepts about Albanian phoneme inventory, also treated Albanian phoneme vowel system. From this perspective, another aim of the study is to compare the Kristoforidhi’s concept with Albanian and foreign linguists, as A. Dodd, Jorgji Gjinari Rexhep Ismaili, M. Halimi, G.S.Louman, N.S Trubeckoi, V. Polak, in order to evaluate Kristoforidhi’s ideas and concepts. Based on these ideas, Kristoforidhi’s concept about Gheg vowel system is very close to the concepts of different albanologists, but also Albanian scholars as well. We may admit that Kristoforidhi’s concept is very close to the contemporary concepts of this nature, therefore, the classification of Gheg vowel system.